Continuous flow synthesis of micron size silica nanoparticles: parametric study and effect of dosing strategy - Jundale, Rajashri; Bari, Atul; Thara, Chinnu; Kulkarni, Amol (Journal of Flow Chemistry, 2018)
This work for the first time reports continuous flow synthesis of silica nano-particles of size over 1 mu m using a simple tubular reactor. The systematic approach involves the study of effect of various parameters like: ammonia concentration, water concentration, electrolyte concentraton, temperature, solvent, residence time and mode of TEOS injection over a wide range. A combination of ethanol and butanol was used as the medium with relatively lower polarity. Various process parameters were optimized to obtain highly monodispersed particles of size up to 600 nm and high yield (up to 90%). Attempts of reducing the reaction time by increasing temperature or concentrations of any of the reagents resulted in significant polydispersity and even in the formation of random shape agglomerates. At the optimized conditions almost complete conversion of TEOS happenned within 40 min and further growth of particles was achieved by adding TEOS using multipoint injection approach. While multipoint dosing resulted in the formation of very small number of secondary particles, the larger particles continued to grow beyond 800 nm. Further reduction in the polarity of reaction medium was achieved by adding 20% v/v of toluene, which without changing homogeneity of the solution resulted in particles as large as 0.9-1.1 mu m.
Keywords: Flow synthesis; Multipoint injection; silica; TEOS; Tubular reactor

Continuous flow synthesis of metal nanowires: protocols, engineering aspects of scale-up and applications - Sonawane, Jayesh R.; Jundale, Rajashri; Kulkarni, Amol A. (Materials Horizons, 2025)
This review comprehensively covers the translation from batch to continuous flow synthesis of metal nanowires (i.e., silver, copper, gold, and platinum nanowires) and their diverse applications across various sectors. Metal nanowires have attracted significant attention owing to their versatility and feasibility for large-scale synthesis. The efficacy of flow chemistry in nanomaterial synthesis has been extensively demonstrated over the past few decades. Continuous flow synthesis offers scalability, high throughput screening, and robust and reproducible synthesis procedures, making it a promising technology. Silver nanowires, widely used in flexible electronics, transparent conductive films, and sensors, have benefited from advancements in continuous flow synthesis aimed at achieving high aspect ratios and uniform diameters, though challenges in preventing agglomeration during large-scale production remain. Copper nanowires, considered as a cost-effective alternative to silver nanowires for conductive materials, have benefited from continuous flow synthesis methods that minimize oxidation and enhance stability, yet scaling up these processes requires precise control of reducing environments and copper ion concentration. A critical evaluation of various metal nanowire ink formulations is conducted, aiming to identify formulations that exhibit superior properties with lower metal solid content. This study delves into the intricacies of continuous flow synthesis methods for metal nanowires, emphasizing the exploration of engineering considerations essential for the design of continuous flow reactors. Furthermore, challenges associated with large-scale synthesis are addressed, highlighting the process-related issues. This review comprehensively covers the translation from batch to continuous flow synthesis of metal nanowires (i.e., silver, copper, gold, and platinum nanowires) and their diverse applications across various sectors.